2010
DOI: 10.1515/hf.2010.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of products from the oxidation of technical lignins by oxygen and H3PMo12O40 in water and aqueous methanol by size-exclusion chromatography

Abstract: One kraft lignin and two lignosulfonates were oxidized in aqueous acidic solutions containing a polyoxometalate (POM). The degradations were carried out in H 2 O or MeOH/ H 2 O mixtures in the presence of oxygen. The treatment with aqueous H 3 PMo 12 O 40 led to the dissolution of the studied lignins in the acidic medium (pH 1-2) and to the formation of up to 6.5 wt% vanillin and 6.2 wt% methyl vanillate based on the weight of dry lignin. The lignin oxidation products were analyzed by size-exclusion chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Wayman and Lora 21 first reported that certain aromatic Fig. 1 Scheme for reactions of lignin in acidic media adapted from Voitl et al 15 (a) cleavage of β-O-4 bond and formation of carbocation; 16 (b) elimination of β-proton giving rise to an enol ether; 16 (c) acid hydrolysis of enol ether; 16 (d) repolymerisation reaction. 17 compounds can act as scavengers in the autohydrolysis of aspen and increase the yield of organic solvent-extractable lignin, allowing to obtain a highly delignified pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Wayman and Lora 21 first reported that certain aromatic Fig. 1 Scheme for reactions of lignin in acidic media adapted from Voitl et al 15 (a) cleavage of β-O-4 bond and formation of carbocation; 16 (b) elimination of β-proton giving rise to an enol ether; 16 (c) acid hydrolysis of enol ether; 16 (d) repolymerisation reaction. 17 compounds can act as scavengers in the autohydrolysis of aspen and increase the yield of organic solvent-extractable lignin, allowing to obtain a highly delignified pulp.…”
Section: Introductionmentioning
confidence: 99%
“…Due to economic and environmental reasons, production of vanillin from lignosulfonates is a declining process (Sixta 2006). Therefore, Rudolf von Rohr and co-workers investigated an alternative process using kraft lignin as feedstock (Voitl et al 2009;Voitl and Rudolf von Rohr 2010;Werhan et al 2011). Kraft lignin is a by-product of the kraft process, which is presently the most prominent pulping process (Auhorn and Niemela 2007).…”
Section: Lignin Oxidationmentioning
confidence: 99%
“…The presence of methanol was found to be necessary to minimise condensation reactions by coupling with reactive intermediates, giving a fifteen-fold enhancement in yield to give approximately 6% vanillin and 6% methyl vanillate [309].…”
Section: Acid Hydrolysismentioning
confidence: 99%